Reading Mesolithic Human Tracks with a Multi Method Approach in the Paul Ambert gallery of Aldène cave (Cesseras, Hérault, France) - Pastoors, Andreas; Lenssen-Erz, Tilmann; Ciqae, Tsamgao; Kxunta, /Ui; Thao, Thui; Galant, Philippe; Weiß, Marcel; Uthmeier, Thorsten (Quartär. Internationales Jahrbuch zur Eiszeitalter- und Steinzeitforschung / International Yearbook for Ice Age and Stone Age Research, 2024)
The richness of Mesolithic footprints in the Paul Ambert gallery of Aldène cave (Hérault, France) has been known for a long time. As part of a multidisciplinary project, the footprints were studied in 2018 by indigenous ichnologists from Namibia. The results of their qualitative morpho-classificatory analyses are presented and complemented by the results of a quantitative morphometric approach. Through this set-up, the results of the two approaches add up to a more comprehensive picture of the footprints in Aldène. According to this, a group of about 25 Mesolithic people visited Aldène once to explore the Paul Ambert gallery. The group was composed of adults, adolescents and children of both sexes. Based on the reconstructed body sizes of the adult trackmakers, they corresponded to the average body size of adult Mesolithic Europeans. The group was not close together as a unit, but split up into different small groups. On the basis of the footprints, differences in behaviour on the way into the cave and the way out of the cave can be seen. On the way in, no member of the group carried anything additional with them. This changed on the way back, where eight adults and adolescents carried something, even though it is not possible to find out what this was exactly. Nevertheless, all evidence points at the possibility that the small children were carried on the shoulders, due to the fact – in the light of the reading of their tracks – they were in a hurry to leave the cave with considerably increased walking speed. The reason for this behaviour could be the "stop on autonomy" assumed by the analysis of the torch traces. After about 500 metres of intensive exploration of the Paul Ambert gallery, about 50 % of the torches brought along had been used up and they had to start walking back. The observation that the walking speed almost doubled on the way out testifies to the urgency of the lighting management problem that had arisen, which has obviously been solved by leaving the cave quickl